Identification of pig DNA using loop-mediated isothermal amplification - Rungruang, Nattakorn; Phapugrangkul, Pongsathon; Kaewpa, Dolnapa (Progress in Applied Science and Technology, 2017)
Loop-mediated isothermal amplification (LAMP) assay and LAMP primers were developed in this study to detect mitochondrial DNA (mtDNA) of pig. The specific LAMP primers were designed from cytochrome b (cyt b) mtDNA of pig that composed of two inner primers (FIP, BIP) and outer primers (F3, B3). The FIP and BIP primers are tandem primers used for loop amplification. The FIP primer set is composed of the forward primer (F2) and the reverse F1c primer linked by additional 4 nucleotide bases, TTTT. The BIP primer set is composed of the reverse primer (B2) and the forward B1c primer linked by TTTT. All LAMP primers recognized six separate regions within target DNA. The cyt b mtDNA was amplified at a range of temperature 57-60oC using Bst DNA polymerase for 60 min with 1 ng of DNA from meat samples. The specificity of LAMP primers was performed using DNA from four meat species (pork, cattle, chicken and duck). The LAMP product was successfully amplified only from cyt b gene of pig whereas no amplified genes was detected from other species. These suggest that the LAMP assay studied was suitable for identifying pig DNA in meat samples.